Qaujimajatuqangit and social problems in modern Inuit society. An elders workshop on angakkuuniq - Oosten, Jarich; Laugrand, Frédéric (Études/Inuit/Studies, 2002)
AbstractThis paper discusses the main results of a workshop on "Integrating Inuit Qaujimajatuqangit into methods of social control" that was held in Rankin Inlet in July 2000. The workshop was set up from an anthropological perspective to record the views of Inuit elders on social control and angakkuuniq (shamanism). In many respects the results of the workshop confirm current trends and efforts to strengthen the involvement of Inuit communities in the judicial processes, especially with respect to minor offences. Today Inuit traditional knowledge and values are rapidly eroding. Many knowledgeable elders who grew up in the nomadic period and in contact with shamans are now passing away and with them disappears the knowledge of the great traditions of angakkuuniq and related beliefs and practices. Hence there is an urgent need to record knowledge from Inuit elders with due attention to its richness and local variation.